2022
DOI: 10.1002/wjo2.9
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic sinusitis: A state‐of‐the‐art review

Abstract: Odontogenic sinusitis (ODS) is more common than historically reported, and is underrepresented in the sinusitis literature. ODS is distinct from rhinosinusitis in that it is infectious sinusitis from an infectious dental source or a complication from dental procedures, and most commonly presents unilaterally. ODS clinical features, microbiology, and diagnostic and treatment paradigms are also distinct from rhinosinusitis. ODS evaluation and management should generally be conducted by both otolaryngologists and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 56 publications
(180 reference statements)
3
25
0
1
Order By: Relevance
“…Odontogenic infection involvement has been implicated in approximately 70% of cases of unilateral paranasal sinusitis; however, it is not exclusively because recent studies have reported the occurrence of bilateral OS (Matsumoto et al, 2015;Pokorny et al, 2013). In computed tomography, OS findings are represented as unilateral maxillary sinus opacification and the presence of overt maxillary dental pathology (Craig JR, 2022). To final diagnosis, the interrelation between medical and dentists is critical to classify and confirm the cause of this condition, in order to minimize further complications (Wuokko-Landen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Odontogenic infection involvement has been implicated in approximately 70% of cases of unilateral paranasal sinusitis; however, it is not exclusively because recent studies have reported the occurrence of bilateral OS (Matsumoto et al, 2015;Pokorny et al, 2013). In computed tomography, OS findings are represented as unilateral maxillary sinus opacification and the presence of overt maxillary dental pathology (Craig JR, 2022). To final diagnosis, the interrelation between medical and dentists is critical to classify and confirm the cause of this condition, in order to minimize further complications (Wuokko-Landen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A combination of medical and surgical approaches was required to treat such association. Concomitant endoscopic management of associated CRS was performed to ensure complete infection resolution and prevent recurrence and complications [18,19]. As pan CRS was present in 67%, working through the natural ostia in ESS; allowed control and drainage of inflammation with the preservation of Schneiderian membrane barriers.…”
Section: Discussionmentioning
confidence: 99%
“…The flora of chronic OS is characterized by the predominant presence of anaerobes such as Gram-negative bacilli, Peptostreptococcus , and Fusobacterium spp., but aerobes can also be encountered, such as Streptococcus c. alpha-hemolytic , Streptococcus c. microhemolytic, Staphylococcus aureus [ 36 ]. Various studies regarding the bacterial species involved report the presence of more than 158 species and several fungi species [ 37 , 38 , 39 ].…”
Section: Microbiologymentioning
confidence: 99%
“…Intraradicular bacteria and fungi that may cause secondary periapical lesions are Streptococcus, Propionibacteriu , and Candida spp., in particular, Candida albicans [ 16 , 41 , 42 , 43 , 44 ]. In periradicular pathology it is difficult to identify the aetiology of the lesions because the bacteria can be extraradicular and diffuse to the periapical area [ 38 , 42 , 43 , 44 ]. This fact is confirmed by bacteria commonly found in abscesses or fistulas, which are consequences of secondary periapical lesions [ 44 , 45 ].…”
Section: Microbiologymentioning
confidence: 99%
See 1 more Smart Citation